You are on page 1of 6

Mathematical Induction

William Cherry

February 2011

These notes provide some additional examples to supplement the section of the text on mathe-
matical induction.
Inequalities. It happens that often in mathematics, the more freedom one has in creating
a solution, the more difficult it is to solve a problem. Often the easiest problems to solve are
those where there is really only one way to get to the solution. In particular, this means that it is
often more difficult to prove an inequality than an equality. Because your textbook does not work
through examples of how to use induction to prove inequalities and yet these can be some of the
more difficult exercises, these notes are intended to provide some examples of using induction to
prove inequalities.

Proposition 1. For every n N, we have n2 + 6n + 7 < 20n2 .

Proof by induction. Let P (n) be the proposition n2 + 6n + 7 < 20n2 .


Base Step. We check P (1), which says 12 + 6(1) + 7 < 20(1)2 . The left-hand-side is 14 and the
right hand side is 20, so P (1) is true and the base step is complete.
Induction Step.
Assume: n2 + 6n + 7 < 20n2 .
Show: (n + 1)2 + 6(n + 1) + 7 < 20(n + 1)2 .
We will begin with the left-hand-side of the inequality we want to show because this is the more
complicated looking side:

(n + 1)2 + 6(n + 1) + 7 = n2 + 2n + 1 + 6n + 6 + 7 [multiply out]


2
= (n + 6n + 7) + (2n + 7) [group terms to make use of our assumption]
< 20n2 + (2n + 7) [using our induction assumption]
2
= 20n + 2n + 7
< 20n2 + 40n + 7 [since 2n < 40n]
2
< 20n + 40n + 20 [since 7 < 20]
2
= 20(n + 2n + 1) [factor out 20]
= 20(n + 1)2 . [factor]

Thus, (n + 1)2 + 6(n + 1) + 7 < 20(n + 1)2 , which is what we needed to show.

Remark. When we do a proof like this, it is important that all of our inequalities go the same
way. In this case, they were all <. We may not mix < and >.

1
Mathematical Induction 2

Proposition 2. For every natural number n 12, we have 5n < n!.

Proof by induction.
Base Step. In this case, we only claim the inequality is true for n 12, so that makes our base
step n = 12. Thus, we need to check whether 512 < 12!. Using a calculator or computer (or a lot
of patience), we determine that

512 = 244, 140, 625 and 12! = 479, 001, 600,

and thus we see that the base step is true.


Induction Step.
Assume: 5n < n!.
Show: 5n+1 < (n + 1)!.
Well start with the left-hand-side of what we are trying to show:

5n+1 = 5 5n [re-write so we can use our assumption]


< 5 n! [since 5n < n! by our induction assumption]
< (n + 1) n! [since n + 1 > 5 (remember n 12)]
= (n + 1)!. [simplifying]

Hence, 5n+1 < (n + 1)! as required.

Remark. This last example also shows the necessity of the base step. Notice that the only thing
we needed in the induction step was that n + 1 > 5, so the induction step works as long as n > 5.
However, 56 = 3125 and 6! = 720, so the proposition is not true for n = 6. We really need the
base step too for our proof to be valid.
Sometimes we might have to prove several inequalities in order to get to the one we want. For
example, suppose we want to prove n3 < 2n . If we take a look at the induction step, it would go
something like this:

Assume: n3 < 2n .
Show: (n + 1)3 < 2n+1 .

If we now start working with what we want to show, we get something like

(n + 1)3 = n3 + 3n2 + 3n + 1 [multiply out]


< 2n + 3n2 + 3n + 1.

But, now we are kind of stuck. If, however, we somehow knew that 3n2 + 3n + 1 < 2n , we could
continue:

2n + 3n2 + 3n + 1 < 2n + 2n
= 2 2n
= 2n+1 .

Well, we should then try to prove 3n2 + 3n + 1 < 2n , which we can also do by induction, after
taking another detour.
Mathematical Induction 3

Proposition 3. For each naturual number n 6, we have 6n + 6 < 2n .

Proof by induction.
Base Step. When n = 6, we have

6(6) + 6 = 42 < 64 = 26 .

Induction Step.
Assume: 6n + 6 < 2n .
Show: 6(n + 1) + 6 < 2n+1 .
Now,

6(n + 1) + 6 = 6n + 6 + 6
< 2n + 6 [using our induction assumption]
<2 +2n n
[since 6 < 2n when n 3]
= 2 2n = 2n+1 ,

as was to be shown.

Proposition 4. For each natural number n 8, we have 3n2 + 3n + 1 < 2n .

Proof by induction.
Base Step. When n = 8, we have

3(8)2 + 3(8) + 1 = 217 < 256 = 28 ,

and so the base step is true.


Induction Step.
Assume: 3n2 + 3n + 1 < 2n .
Show: 3(n + 1)2 + 3(n + 1) + 1 < 2n+1 .
Starting with the left-hand-side of what we need to show, we have

3(n + 1)2 + 3(n + 1) + 1 = 3(n2 + 2n + 1) + 3n + 3 + 1


= 3n2 + 6n + 3 + 3n + 3 + 1
= (3n2 + 3n + 1) + (6n + 6) [Re-group to apply induction assumption]
n
< 2 + (6n + 6) [By our induction assumption]
n n
<2 +2 [By Proposition 3]
= 2 2n = 2n+1 ,

as required.

We are now finally able to get to the inequality we wanted.

Proposition 5. For each natural number n 10, we have n3 < 2n .

Proof by induction.
Base Step. When n = 10, we have

103 = 1000 < 1024 = 210 ,


Mathematical Induction 4

and so the base step holds.


Induction Step.
Assume: n3 < 2n .
Show: (n + 1)3 < 2n+1 .
Starting with the left-hand-side,

(n + 1)3 = n3 + 3n2 + 3n + 1 [multiply out]


n 2
< 2 + 3n + 3n + 1 [using our induction assumption]
n n
<2 +2 [by Proposition 4]
= 2 2n = 2n+1 ,

and so we are done.

Generalized Strong Induction. The method of proof by induction can be generalized as


follows. Suppose we have a proposition P (n) and suppose we want to prove that P (n) is true for
all integers n such that n m for some integer m. Suppose we also prove the following:

Generalized base step: There exists an ` Z such that P (j) is true for j = m, m + 1, . . . , `.

Strong induction step: For each k Z such that k `, we have

(P (m) P (m + 1) P (m + 2) P (k)) P (k + 1).

In analogy with my stairstep explanation in class, this goes as follows. For the generalized base
step, suppose we can show that we can get to any of the first five stairs on the infinite stair case.
Now suppose that we can show that if we can get all the stairs before the k + 1-st step, then we
can also get to k + 1-st step. Then we can climb all the stairs. Imagine, for example, that in order
to go up a stair, we need to both stand on the stair before, and use the assistance of a pole resting
on the stair before that.
In practice, strong induction often works as follows. We do a double base step, for example,
we show P (1) and P (2) are true. Then, for the induction step, we show that P (n 1) and P (n)
together imply P (n + 1). That is, we use the assistance of two previous stairs to help us climb to
the next step.
Here is an example.

Proposition 6. For each natural number n, there exist natural numbers a and b such that
5n = a2 + b2 .

Proof by strong induction.


Base step. We will do a double base step, allowing us to go two steps back in our induction
step.
For n = 1, we can choose a = 1 and b = 2 and we have

51 = 5 = 1 + 4 = 12 + 22 .

For n = 2, we can choose a = 3 and b = 4, since

52 = 32 + 42 .
Mathematical Induction 5

Induction Step. For this proof, instead of showing that P (n) implies P (n + 1), we will show
that P (n 1) implies P (n + 1). Because we are skipping over a step each time, we need the
double base step above.
Assume: There exist a and b in N such that 5n1 = a2 + b2 .
Show: There exist c and d in N such that 5n+1 = c2 + d2 .
We start with the left-hand-side, and write 5n+1 = 52 5n1 . Then, we use our induction
assumption that 5n1 = a2 + b2 . So, we then have

5n+1 = 52 5n1 = 52 (a2 + b2 ) = 52 a2 + 52 b2 = (5a)2 + (5b)2 .

Thus, we can choose c = 5a and d = 5b to get

5n+1 = c2 + d2 ,

and our proof is complete.

Fibonacci numbers. The Fibonacci numbers are defined recursively as follows:

F0 = 0, F1 = 1, and Fn = Fn1 + Fn2 for n 2.

So, for instance, the Fibonacci numbers start out

0, 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, . . .

where the first two are 0 and 1 and each successive number is obtained by adding the previous
two. Problems involving Fibonacci numbers are natural candidates for going backward two steps.

Proposition 7. For each n = 0, 1, 2, 3, . . . , we have Fn < 2n .

Proof by strong induction.


Base Step. We will verify the inequality for n = 0 and n = 1 for our base step. For n = 0, we
have
F0 = 0 < 1 = 20 .
For n = 1, we have
F1 = 1 < 2 = 21 ,
and so we have verified the inquality for n = 0 and n = 1.
Induction step. Because we have completed a double base step, we are allowed to use two
induction assumptions.
Assumption 1. Fn1 < 2n1 .
Assumption 2. Fn < 2n .
Show. Fn+1 < 2n+1 .
Starting with the definition of the Fibonacci numbers, we have

Fn+1 = Fn + Fn1 [definition of Fn ]


n n1
<2 +2 [Using our two induction assumptions]
n n
<2 +2 [since 2n1 < 2n .]
= 2 2n = 2n+1 .

Hence, Fn+1 < 2n+1 as was to be shown.


Mathematical Induction 6

The method of strong induction can sometimes be used to shorten an induction proof of an
inequalty. Earlier in these notes we proved that n3 < 2n for all natural numbes n 10, but our
proof was rather tedius. Using strong induction, we can shorten our proof.

Proposition 8. For each natural number n 10, we have n3 < 2n .

Proof by strong induction.


Base Step. First, we will do an extended base step:
n n3 2n
10 1000 1024 X
11 1331 2048 X
Induction step.
Assume: n 10 and n3 < 2n .
Show: (n + 2)3 < 2n+2 .

(n + 2)3 = n3 + 6n2 + 12n + 8 [multiply out]


< n3 + n3 + 12n + 8 [since 6 < n]
3 3 3
<n +n +n +8 [since 12 < n2 ]
< n3 + n3 + n3 + n3 [since 8 < n3 ]
= 4n3
< 4 2n [by our induction assumption]
= 2n+2 .

You might also like